2014
DOI: 10.1016/j.pharep.2014.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Statins – Are they anticonvulsant?

Abstract: Statins are the most popular and effective lipid-lowering medications beneficial in hypercholesterolemias and prevention of cardiovascular diseases. Growing evidence supports theory that statins exhibit neuroprotective action in acute stroke, Alzheimer's disease, Parkinson's disease, multiple sclerosis or epilepsy. Hereby, we present available experimental data regarding action of this group of drugs on seizure activity and neuronal cell death. The most commonly examined statins, such as atorvastatin and simva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…In a clinical study, it has been reported that HMG-CoA reductase inhibitor treatment improves cerebral vasomotor reactivity in patients with cerebral small-vessel disease. Furthermore, the effects of statins on the activation of eNOS have been also revealed (Laufs et al, 2002;Kosmidou et al, 2007;Savoia et al, 2011;Zhou et al, 2013;Banach et al, 2014). It has been also shown that the inhibition of NO by using L-NAME reverses the anticonvulsant effect of atorvastatin after penthylenetetrazol-induced seizure Moazzami et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…In a clinical study, it has been reported that HMG-CoA reductase inhibitor treatment improves cerebral vasomotor reactivity in patients with cerebral small-vessel disease. Furthermore, the effects of statins on the activation of eNOS have been also revealed (Laufs et al, 2002;Kosmidou et al, 2007;Savoia et al, 2011;Zhou et al, 2013;Banach et al, 2014). It has been also shown that the inhibition of NO by using L-NAME reverses the anticonvulsant effect of atorvastatin after penthylenetetrazol-induced seizure Moazzami et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…And only simvastatin enhanced episodic-like memory (Ramirez et al, 2011). According to recent studies, lipophilic simvastatin was recommended as the best candidate as an anticonvulsant agent (Banach et al, 2014). The authors have discussed and concluded that the most probable explanation of the observed anticonvulsant properties of statins is their influence on neurosteroid or NO synthesis in the brain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations